TESL graduates and TVET English language teaching readiness: the curriculum perspectives / Faizah Abd Majid, Wan Nurul Elia Haslee Sharil and Muhamad Fairus Kamaruzaman - Abd Majid, Faizah; Haslee Sharil, Wan Nurul Elia; Kamaruzaman, Muhamad Fairus (Universiti Teknologi MARA, 2023)
This paper explores the potential gaps in addressing the competencies of pre-service English teachers by focusing on two main aspects; a) pre-service English teachers’ preparation to teach ‘smart and sharp skills’ in TVET programmes and b) the implications on the current TESL curriculum. Hence, the purpose of the present study is twofold; to determine the elements of ‘smart and sharp skills’ exposure in TESL programme and to identify the pre-service TESL graduates’ readiness to train these skills in the TVET programme. Employing a qualitative research design, the data was obtained through document analyses. The inclusion of ‘smart and sharp’ skills in the TESL programme and their match with the TVET teaching competency became the starting point of the investigation as the findings would be referred to in scrutinizing the TESL graduates’ preparation to train those skills in TVET programme. Existing TESL curriculum documents from three public universities in Malaysia offering TESL programmes formed the units of investigation in the study, particularly in looking at the programme’s learning outcomes (PLOs). Likewise, the Malaysian Quality Agency’s (MQA) Programme Educational Objectives (PEO) for TVET teaching competency was scrutinized in finding a pattern between the PEOs, TESL PLOs and the exposure to ‘smart and sharp’ skills. Thematic analysis was employed in analyzing the data and to confirm its trustworthiness, an inter-rater test of agreement was conducted. Salient findings include the potential of the exposure to ‘smart and sharp’ skills in the existing TESL curriculum and the readiness of the TESL graduates to train those skills in TVET programmes. Based on the findings, several implications and recommendations have been identified and proposed. It is expected that policy makers, curriculum developers and TESL educators could benefit from the findings and implications presented in this paper. Further research focusing on the training effectiveness of ‘smart and sharp’ skills for TVET students could also be considered.